Les droits et les devoirs fondamentaux de la femme dans l'église - Le Tourneau, Dominique (Studia canonica, 2015)
Some may feel it is good form to accuse the Catholic Church of being anti-feminist and of giving prominence to men in its organization and its operations. Does such discrimination against women really exist in the Church? What about its fundamental rights and obligations, proclaimed by the Second Vatican Council and taken up again by the present legislation, Latin as well as Eastern, that consecrates the radical equality of all the baptized and, therefore, of women and men? In order to answer these questions, a historical reminder is necessary, which first describes Jesus' attitude towards women and demonstrates the complementarity of man and woman in Christian anthropology; it then leads to a realization that it is at the time of the Renaissance that the place and the role of women in civil society began to lose of their importance, the turning point being with the Roman de la Rose. The Church restrains this evolution, until the proclamation by Vatican II of the equality among the baptized. The author also deals with the true concepts of discrimination and equality. In a second part, he comes to the application of the fundamental equality between men and women in the Church, in relation to offices assumed by women in the exercise of the tria munera docendi, sanctificandi et regendi, an area that still allows for certain inequalities. The author refutes the need to create a 'status of women', which he believes truly marks that a woman is different from a man. He finally broaches the question of non-accession of women to ministerial priesthood, in the absence of any right to be ordained, which results in men and women remaining equal in nature, in rights, and in obligations. A last point deals with women and the diaconate. The author looks at the present legislation without indulgence and underlines its deficiencies.